Emotional regulation in 4- and 5-year-old children during the pandemic: protective factors and risks in a private institution in Costa Rica - Ureña Pinto, Melissa (2024)
The COVID 19 pandemic generated consequences for children, reflecting the social and psychological impact worldwide due to changes such as the absence of face-to-face classes and the transfer of education to homes. This not only represented a challenge for children, but also for families and educational institutions, who are in charge of the development of children's emotional regulation. This qualitative research based on grounded theory, aims to analyze the role of protective and risk factors related to the development of emotional regulation in children aged 4 and 5 years that were present during the context of remote education due to the COVID-19 pandemic. in 2020. For this, 5 interviews were conducted virtually with staff from an educational institution, as well as with 2 mothers of students who were in preschool in 2020, and a focus group with 5 mothers. In addition, an in-person activity was carried out with two groups of children, lasting approximately 40 minutes with each group, who were taught the story of the “Color Monster” to talk and identify emotions, as well as a space to paint and develop a dialogue, which allowed us to know their perspective of the pandemic, and the labeling of emotions they have. Protective and risk factors were also identified, such as listening to and discussing emotions, communication between family and school, support in the educational process, among others. It is concluded that, similar to international studies, this situation caused changes in daily routines, eating, sleeping, socialization with peers, and childhood emotions. For families it meant assuming a new role as educators for which they were not prepared. Both teachers and families highlighted the overload experienced. Protective and risk factors were identified such as listening to and discussing emotions, communication between family and school, support in the educational process, among others.